Desinfecção solar de águas cinza para aproveitamento agrícola no semiárido-RN - Cavalcante, Fernanda Lima (Universidade Federal Rural do Semi-Árido, 2017)
The high incidence of waterborne diseases is attributed to the inadequacy of sanitary sewage systems in Brazilian rural areas. The use of solar radiation has low-cost, easy operation and do not use chemicals in wastewater disinfection for agricultural use. Given the above, this study aimed at developing and validating a solar reactor for the disinfection of gray water from rural areas in the semiarid region, aiming at the reuse of the effluent. The experiments were conducted in the experimental area of the Federal Rural University of the Semi-Arid region in Mossoró, state of Rio Grande do Norte. The gray water treatment plant consists of septic tank, anaerobic filter and solar reactor. In the solar reactor, 0.1 m layers of gray water were exposed to solar radiation during the period between 8:00 AM to 4:00 PM, and aliquots were taken every two hours. The experimental tests were performed from July to December 2015, in order to evaluate the efficiency of solar disinfection by means of pH, dissolved oxygen, temperature, electrical conductivity, total suspended solids, turbidity, total coliforms, E. coli and helminth eggs. At the same time, the following environmental variables were monitored: air temperature and global solar radiation. For enumeration of helminth eggs, we used the modified Bailenger technique. For determination of fecal coliforms, we used the Colilert method. Data were subjected to descriptive statistics and analysis of variance for all analyzed characteristics. Multivariate analysis such as principal component analysis and hierarchical cluster analysis were also applied. A multiple regression analysis proposed a mathematical model that represents the inactivation of pathogens through solar disinfection. The results showed that the 8-hour solar exposure time was not enough to reduce the E. coli population to the point of allowing unrestricted reuse in irrigation, requiring longer exposure times or reduction in effluent color and turbidity. Principal component analysis summarized the initial 11 variables to 7 variables, explaining 79.46% of the total variance. The analysis of hierarchical clustering indicated the formation of four distinct groups, with determinant influence of seasonality and the time of exposure to solar radiation. According to the regression analysis, the most important variables in the solar disinfection process were cumulative solar radiation and conductivity
Keywords: Reator solar; Resíduo líquido; Agentes patogênicos; Reúso na agricultura; Solar reactor; Liquid residue; Pathogens; Reuse in agriculture; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO